The line model of form and emotion - Lewis Urquhart; Andrew Wodehouse (Human Technology, 2018)
This paper introduces a new model of form, emotion, and semantics through a process of form abstraction utilizing lines. Understanding the emotional and semantic value of form is a complex task, and many theories have been developed. Analyzing the visual arts through line relationships and interactions is a conceptually novel approach and offers new avenues for advancing studies in form theory, theories of emotion and perception, and design generally. By examining literature in visual perception, form theory, and emotion, and by historically analyzing changes in form through the aesthetic arts and then reducing these aesthetic elements into basic linear foundations, we developed the line model of form and emotion. This preliminary model presents form at its structurally most abstract, simplifying three dimensionally defined shapes into line relationships, and portrays their emotive and semantic associations for human observers. The model also visualizes the historical changes in form and emotional and semantic meaning across time, from the 18th century to the present day.